Význam volných radikálů a antioxidantů sportovní záteze - Holecek, V; Liska, J; Racek, J; Rokyta, R (Ceskoslovenska fysiologie, 2004)
Sport performance is followed by a high production of free radicals. The main reasons are reperfusion after the previous imbalance between the increased need of the organism and the ability of blood supply by oxygen, increased production of ATP, decomposition of the cells particularly white blood cells, oxidation of the purin basis from DNA, stress, output of epinephrine release of free iron, increased temperature in the muscle and its inflammation, and the reception of free radicals from external environment. Peroxidation of lipids, proteins, DNA and other compounds follows the previous biochemical steps. Antioxidants are consumed by free radicals, antioxidative enzymes are released into blood plasma, intracellular calcium is increased, the production of nitric oxide rises, the levels of hydrogen peroxide and hypochlorous acid increase. These penetrate through the membranes and oxidatively damage the tissues. Training improves the ability of the organism to balance the increased load of free radicals. The damage can be lowered by the application of a mixture of antioxidants, the most important are vitamin C, A, E, glutathione, selenium, carnosine, eventually bioflavonoids and ginkgo biloba. The lack of antioxidants can significantly diminish the sport performance and therefore the supplementation with antioxidants is for top sportsmen but also for aged people advisable.
Keywords: tělesná námaha; Physical Exertion; lidé; Antioxidants; antioxidancia; Sports; sporty; volné radikály; Free Radicals; Humans